Pengembangan Media Pembelajaran Berbasis Web ‘MAHARA’ untuk Meningkatkan Keterampilan Maharah Qira’ah Mahasiswa - Nursa'adah, Diva; Afifah, Anis; Nurul Aini Lathifah, Siti (Kartika: Jurnal Studi Keislaman, 2025)
The learning of Maharah Qira’ah at the higher education level still faces challenges, particularly the low motivation and participation of students due to the limited use of interactive digital media. This academic concern encouraged the researcher to design a new medium that can effectively support Maharah Qira’ah learning. The aim of this study is to develop a website-based learning media integrated with WordWall, called “MAHARA”, and to assess its validity and effectiveness in improving students’ reading skills. This research employed the Research and Development (R&D) method with the ADDIE model, consisting of the stages of analysis, design, development, implementation, and evaluation. The subjects were 16 second-semester students of the Arabic Language Education Program at Institut Attanwir Bojonegoro. Data were collected through observation, interviews, questionnaires, pre-tests, and post-tests, analyzed using both qualitative and quantitative approaches. The results indicated that “MAHARA” was categorized as highly valid with validation scores of 90% from media experts, 96% from material experts, and 92% from instructional experts. Students’ average scores increased from 72.50 (pre-test) to 96.25 (post-test), with the Paired Sample T-Test showing a significance value of 0.002 < 0.05, proving its effectiveness. The implication is that “MAHARA” can serve as an innovative alternative in Arabic learning, particularly in Maharah Qira’ah, and foster the integration of interactive digital media in higher education.